Weather-based empirical model to predict infective sporidial stage of Tilletia indica during wheat crop season - and S.S. HUNDAL, GURBIR KAUR, SATVINDER KAUR* (Indian Phytopathology, 2007)
Investigations on the effect of weather parameters on the survival of colony formed by the germinated teliospores of Tilletia indica (Mitra) Mundkur and the infective sporidial stage were made in the wheat field at Ludhiana. Actively growing colonies incubated in the wheat field remained viable up to 19 days, when mean temperature for this period was 10°C (minimum), 22°C (maximum) and RH 58-94%. Best fit third degree polynornlal functions explained the observed variation with maximum temperature (X). in the survival of T.indica colony (y) = -0.025X3+ 2.197X2- 64.01X+ 629.45, (R2 = 0.95). The sporidia were produced through out the wheat crop season and the number formed peaked during heading of wheat crop. Maximum number formed were 170 per 200x, when the colony was incubated from 5pm to 9am ( night regime), when temperature was 7.4-8.2 °c, RH 100% and GOD 11.2 °c days, in both the years. In the day regime (9am - 5pm), highest number of sporidia detected was 40 sporidia per 200x, when temperature was 18.4 °c (maximum), 56% RH and GOD 11.6°C days in 2004. Best fit polynomial equations for highest sporidial counts (y) were obtained with maximum temperature (X), for night regime it was: Y=0.3403X3_22.63X2+ 482.87X3174.6 (R2=0.45) and for the day regime Y=0.1835X3_12.628X2+ 282.64X- 2030.3 (R2 = 0.62), which validated the observed and expected number of sporidia formed, although R2value was low as compared to the model which was developed using mean weather parameters for the various c asses of sporidia produced V= -10.475X3+ 73.33X2- 126.59X + 172.6, when R2=0.99. Number of favourable days (X) when optimum conditions were prevalent for the maximum production of the infective stage were identified in the agro-metrological data from 1996-2005, during heading of wheat and correlated Significantly with incidence of Karnal bunt (Y) observed in the farmers field and best fit polynomial equation Y = -0.0207X3 + 0.157X2- 0.0606X + 0.0187 (R2 = 0.99), developed explained 99% variations.